Pola Umum Bimbingan dan Konseling di Sekolah Dasar - Fadiyatun Nufus; Annisa Annisa; Siti Aisyah; Maemunah Maemunah; Titi Sunarti (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
Guidance and counseling serve as a fundamental component of the educational process at the elementary school level, playing a crucial role in supporting students’ holistic development. This study aims to outline the general implementation patterns of guidance and counseling services in elementary schools and to analyze their contribution to students’ personal, social, academic, and career growth. A descriptive qualitative approach was employed, utilizing a literature review method. Data were gathered through an examination of relevant scientific journals, reference books, and educational regulations, with particular attention to the Regulation of the Minister of Education and Culture Number 111 of 2014. The findings indicate that the general pattern of guidance and counseling in elementary schools consists of four main service areas implemented in an integrated and continuous manner. These services contribute to helping students manage emotions, develop social skills, enhance learning motivation and academic achievement, and recognize interests and potentials from an early age. Therefore, optimizing the implementation of guidance and counseling services in elementary schools is essential to support the achievement of holistic educational goals.